Influence of carbonisation temperature on the gasification of Acacia wood chars by carbon dioxide - Kumar M.; Gupta R.C.; Sharma T. (My University, 2025)
Carbon dioxide gasification rates of various Acacia wood chars, prepared at temperatures in the range 400-1200°C, were measured thermogravimetrically at 810, 860, 900 and 960°C. The effects of char formation (i.e., carbonisation) temperature, flow rate of CO2 and reaction temperature on the rates were evaluated. Reactivity was determined from mass conversion data. Results indicate that the wood carbonisation temperature had a notable influence on reactivity. With increasing char formation temperature the reactivity was reduced. © 1992.